The GLP-1 receptor agonist liraglutide inhibits necroptosis and neuroinflammation in a mouse model of Parkinson’s disease with diabetes co-morbidity - Xiaomin Zhang; Pengyang Du; Bo Bai; Peng Feng; Xia Lian; Christian Hölscher; Yongqing Wang; Guofang Xue (Frontiers in Neuroscience)
ObjectiveTo investigate the effects of the glucagon-like peptide-1 (GLP-1) receptor agonist liraglutide on motor function, necroptosis, and neuroinflammation in the brain in mice with diabetic Parkinson’s disease (PD) and its possible mechanism.MethodsWe prepared a diabetic model with streptozotocin, followed by 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine-induced diabetic PD model, along with liraglutide or saline intervention, and the control group with equal volume saline. After that, body weight and blood glucose of each group mice were measured, and the open field experiment and gait analysis experiment were performed to detect the motor and non-motor symptoms of mice, western blotting and immunohistochemistry experiments were performed to test the levels of necroptosis-related proteins tumor necrosis factor-α (TNF-α), receptor interacting serine/threonine kinase 1 (RIP1) and neuroinflammation-related proteins nuclear factor kappa-B p-p65 (NF-κB p-p65), nuclear factor kappa-B p65 (NF-κB p65), interleukin-1 beta (IL-1β), and monocyte chemoattractant protein-1 (MCP-1).ResultsThe GLP-1 receptor agonist liraglutide inhibited necroptosis and neuroinflammation via TNF-α signaling in diabetic PD mice, decreasing blood glucose and improving motor function and mood. Compared with the control group, the blood glucose of diabetic PD mice increased, and the total distance and resting time in the central area decreased in the open field tests, stride length and overall run speed reduced in the gait analysis experiments, stance time and stride width increased, and the levels of necroptosis-related proteins such as TNF-α and RIP1, as well as neuroinflammation-related proteins including NF-κB p-p65/p65, IL-1β, and MCP-1 increased. Compared with the diabetic PD mice on the 7th day, the mice in the model group on the 21st day showed reduced motor activity and more severe brain injury. After administration of liraglutide, these impairments were reversed.ConclusionIn the diabetic PD model, liraglutide is neuroprotective by reducing necroptosis and neuroinflammation through the TNF-α signaling pathway.